Developing Ball Dribbling And Passing Skills Using The Integrative And Reciprocal Methods Of Emerging Footballers (Eurasian Journal of Humanities and Social Sciences, 2022)
The purpose of the study was to determine the influence of the two learning methods (reciprocity and inclusion) on the development of running with ball and passing skills, as well as to determine the most effective learning approach for this skills. Following the selection of the experimental curriculum with equal totals, the research sample was chosen from the consisting of thirty players chosen by Al Majer Al Kaber and AlMaimouna Clubs and chosen in the intentional sample that was intended. Where the sample was distributed to the third totals by (10) players for each group, with the first experimental group using the inclusion method, the second experimental group using the reciprocal style, and the third group officer. Following the conclusion of the , the embedding and interchangeable learning approaches were used for the two experimental research groups, and then the results of the post- test were analysed. The researchers determined that the interactive method group is the best group in the speed of the development of ball running and handling skills for junior football players based on the data that were statistically analysed in order to meet the objectives of the research.